PENGARUH BRAND REPUTATION TERHADAP BRAND TRUST, YANG DI MODERASI OLEH SOSIAL MEDIA ( Studi Kasus Pada Pengguna Skintific di Malang) - Maya Alvina Damanik (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The rapid development in today's business world has transformed the brand management landscape, placing a primary focus on the concept of brand reputation. Brand reputation has become one of the most crucial aspects in efforts to build and sustain a competitive position in an increasingly complex market. This research addresses the phenomenon by examining how brand reputation can lead to an increase or decrease in brand trust, taking into account the moderating role of social media. This phenomenon becomes more intricate with the rapid growth of social media usage in conveying consumer information and experiences, creating new challenges in understanding the dynamic interactions among brand reputation, brand trust, and social media.The adopted research method in this study is a quantitative research method, aiming to systematically collect data and generate statistically measurable findings. By distributing questionnaires to 114 respondents and employing data analysis techniques using SPSS software, the research results reveal a significance value (sig) less than 0.05 (0.001 > 0.05) and a t-table value less than the t-test value (1.981 > 2.407). Hence, it can be stated that brand reputation has an influence on brand trust. Furthermore, with a significance value (sig) less than 0.05 (0.002 > 0.05) and a t-table value less than the t-test value (1.981 > 2.401), it can be concluded that brand reputation moderated by social media has an impact on brand trust.